2021
DOI: 10.1111/ajo.13378
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of the need to morcellate in total laparoscopic hysterectomy

Abstract: Background Specimen extraction is a major challenge in total laparoscopic hysterectomy (TLH) and tissue morcellation may be needed to extract a large uterus. Aims The study aims to determine preoperative factors that could predict the need for uterine morcellation in TLH, and also find the best cut‐off values of each measured parameter leading to optimum sensitivity and specificity. Materials and Methods This was a cross‐sectional study of women from August 2019 to May 2020 who underwent TLH, with or without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Two recent studies [21,22] found that the strongest pre-operative predictors Relative Risk (RR) for the need of morcellation were the leiomyoma diameter of >40-44 mm (RR: 3.58), uterine cross-sectional area of >36.5-48.6 cm 2 (RR: 6.38), uterine size in the bimanual exam of >11.5-13 weeks pregnancy (RR: 3.57) and uterine volume of 262 ml. Highlighting, that during the selection of the surgical approach, uterine size plays a major and foremost decisive factor, over patient or surgeon's preference.…”
Section: Plos Onementioning
confidence: 99%
“…Two recent studies [21,22] found that the strongest pre-operative predictors Relative Risk (RR) for the need of morcellation were the leiomyoma diameter of >40-44 mm (RR: 3.58), uterine cross-sectional area of >36.5-48.6 cm 2 (RR: 6.38), uterine size in the bimanual exam of >11.5-13 weeks pregnancy (RR: 3.57) and uterine volume of 262 ml. Highlighting, that during the selection of the surgical approach, uterine size plays a major and foremost decisive factor, over patient or surgeon's preference.…”
Section: Plos Onementioning
confidence: 99%